MANGROVE MONITORING USING NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI): CASE STUDY IN NORTH HALMAHERA, INDONESIA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Community-based ecotourism is an appropriate approach which is effectively preserved mangrove sustainability. As an effort to identify the priority areas of mangrove development, mangrove density levels need to be analyzed. The distribution of mangroves with the lowest average density value needs to be prioritized as a preservation and conservation strategy through community-based ecotourism concept. This article aims to identify the distribution of mangroves using the normalized difference vegetation index (NDVI) model in North Halmahera Regency, Indonesia. Also, discuss the sustainable livelihoods' perspective. This study adopted a mixed-method. Data processing is divided into two stages: first stage, mapping the distribution of mangroves based on density levels; second stage, triangulation. Landsat 8 operational land imager (OLI) in 2013 and 2021 were used as primary data to get the NDVI value, and categorized mangrove density level in Pilawang Cape, Kumo Island, Kakara Island, Maiti Island, and Tagalaya Island. The findings show that Pilawang Cape has the lowest NDVI value. The average NDVI value in 2021 is 0.22 which can be categorized as a rare mangrove forest according to the mangrove standard damage criteria. Thus, Mangrove area in Pilawang Cape needs to be prioritized as a preservation and conservation strategy through community-based ecotourism concept.